The Craft of Programming. - Holmes, Neville (Computer (00189162), 2008)
The article focuses on the development of the role of programmers within the computer industry in the 20th century and calls for changes in the 21st. The evolution of the programmer is described from a machine operator who designed and altered the hardware architecture, to problem solving specialists formulating algorithms, to contemporary roles of higher information theory managers. Calls are offered to regress the trends of computer user interaction, allowing individual users to have more control and knowledge over the processing mechanisms of their computers.